Technical Note: First Use of Endonasal Confocal Laser Endomicroscopy – Feasibility and Proof of Concept - Wenda,Nina (2022)
Abstract Introduction Probe-based confocal laser endomicroscopy (p-CLE) is a method for real-time in vivo visualization of mucosal changes on a cellular level. Due to the size of the endoscopes, it was mainly used in the gastrointestinal tract so far. First investigations on head and neck carcinoma described the oropharyngeal application. The further miniaturization of the laser probe now allows endonasal application and, thus, first experiences with the investigation of endonasal neoplasms. Objectives The aim of the present investigation is to elucidate, based on the morphological criteria validated in the oropharynx, whether these criteria be transferred in a similar way to the endonasal mucosa. Methods We conducted p-CLE (Cellvizio, Paris, France) with intravenous fluorescein staining in endoscopic sinus surgery in a patient with sinonasal inverted papilloma and a histologically confirmed squamous cell carcinoma. We compared the cellular visualization of pathological changes with those of healthy mucosa in the same specimen, and also with our former findings in the oropharynx. Results Endonasal p-CLE proved to be quite feasible in the surgical setting, and the transfer of malignancy criteria in analogy to histological examination could be optically retraced. Furthermore, additional criteria for tissue dignity assessment were obtained. Conclusion Our results suggest that endonasal application of p-CLE represents a valuable extension of the diagnostic repertoire available to date by an additional realtime analysis of the nasal mucosa. This is of particular value in surgically challenging anatomical areas such as the paranasal sinuses.